Ethnopolitics in Eastern European Countries : Implications for National Security - Karolak-Michalska, Magdalena (International Studies in Sociology and Social Anthropology, 2026)
This book is interdisciplinary and competently explains the complex relationship between ethnicity, politics and security in Eastern Europe. Magdalena Karolak-Michalska diagnoses and predicts how the determinants of ethnopolitics are being securitized and what implications this process has for the security of Eastern Europe (Belarus, Moldova, Ukraine). The lack of optimal legal solutions in ethnopolitics and the increased activity of nationalist organizations promote the occurrence of ethnic conflicts and disintegration movements in Eastern Europe. This pioneering monograph also contains a catalog of important recommendations that can be used in improving systems for monitoring ethnopolitical processes and strengthening the security of Eastern Europe.